SUSTAINABILITY ASSESSMENT WITH MULTIDIMENSIONAL SCALING IN THE SUSTAINABLE FOOD YARD PROGRAM (CASE STUDY: SEMARANG CITY) - Nugraha, Fadhil Adi; Ekowati, Titik; Sumarsono, Sumarsono (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Population growth in Semarang City has an impact on the emergence of a food security issue and the high rate of unemployment. The Indonesian government issued a program named the Pekarangan Pangan Lestari or Sustainable Food Yard (SFY) that is expected to solve these problems through urban farming activities. However, the SFY is still experiencing many problems in the field that could threaten its sustainability. This study aims to analyze the sustainability status of the SFY program in Semarang City which consists of the Growth Stage and the Development Stage. The study is descriptive research with a survey method. The study was conducted on 130 sampling farmers in Semarang City that obtained the benefit of the program between 2020-2021. Sample determination used a proportional random sampling method. The data was collected by interview and analyzed using multidimensional scaling. Study results showed that the social, economic, and ecological dimensions of the Growth Stage are less sustainable than the Development Stage’s dimensions. The most sensitive attributes for the social dimension are farmer’s working hours and farmer’s independence. The most sensitive attributes for the economic dimension are product affordability and market demand. The most sensitive attributes for the ecological dimension are water availability and LEISA application. Improvement of sensitive attributes in those dimensions needs to be done to increase the sustainability status of all dimensions in the Growth Stage and the Development Stage of the SFY program in Semarang City.